2020
DOI: 10.1084/jem.20191421
|View full text |Cite|
|
Sign up to set email alerts
|

NK cell–derived GM-CSF potentiates inflammatory arthritis and is negatively regulated by CIS

Abstract: Despite increasing recognition of the importance of GM-CSF in autoimmune disease, it remains unclear how GM-CSF is regulated at sites of tissue inflammation. Using GM-CSF fate reporter mice, we show that synovial NK cells produce GM-CSF in autoantibody-mediated inflammatory arthritis. Synovial NK cells promote a neutrophilic inflammatory cell infiltrate, and persistent arthritis, via GM-CSF production, as deletion of NK cells, or specific ablation of GM-CSF production in NK cells, abrogated disease. Synovial N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
81
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(86 citation statements)
references
References 113 publications
3
81
2
Order By: Relevance
“…More recently, we reported that synovial joint NK cells propagate joint inflammation by secreting the pro‐inflammatory cytokine GM‐CSF 91 (Figure 1b). This occurs in an IL‐18‐dependent manner, and independently of their cytotoxic function or IFN‐γ production 91 . GM‐CSF, in turn, signals to joint‐infiltrating myeloid cells such as neutrophils to upregulate pro‐inflammatory CXCL2, CCL3 and LTβ4, thereby sustaining immune cell recruitment into inflamed joints 91 .…”
Section: Nk Cells In Rheumatoid Arthritismentioning
confidence: 85%
See 2 more Smart Citations
“…More recently, we reported that synovial joint NK cells propagate joint inflammation by secreting the pro‐inflammatory cytokine GM‐CSF 91 (Figure 1b). This occurs in an IL‐18‐dependent manner, and independently of their cytotoxic function or IFN‐γ production 91 . GM‐CSF, in turn, signals to joint‐infiltrating myeloid cells such as neutrophils to upregulate pro‐inflammatory CXCL2, CCL3 and LTβ4, thereby sustaining immune cell recruitment into inflamed joints 91 .…”
Section: Nk Cells In Rheumatoid Arthritismentioning
confidence: 85%
“…Synovial NK‐derived IFN‐γ has also been thought to limit arthritis by inhibiting Th17 polarisation in the CIA model, 100 but this seems questionable given the low IFN‐γ production by RA synovial NK cells 115 . More recently, we reported that synovial joint NK cells propagate joint inflammation by secreting the pro‐inflammatory cytokine GM‐CSF 91 (Figure 1b). This occurs in an IL‐18‐dependent manner, and independently of their cytotoxic function or IFN‐γ production 91 .…”
Section: Nk Cells In Rheumatoid Arthritismentioning
confidence: 97%
See 1 more Smart Citation
“…This has been suggested to occur through NK cell production of GM-CSF ( 7 , 8 ). That GM-CSF produced by NK cells has been shown to potentiate several chronic inflammatory disorders ( 9 ) may indicate involvement of NK cell-neutrophil crosstalk in these diseases. NK cells recruit neutrophils to inflammatory sites through several mechanisms, including the CCL3-CCR5 signaling axis ( 2 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, NK cell production of IFN-γ is critical for the complete elimination of intracellular bacteria by myeloid cells ( Dunn and North, 1991 ; Feng et al, 2006 ; Steinhoff et al, 1991 ). NK cells can also control macrophage polarization in adipose tissue ( Lee et al, 2016 ; O’Sullivan et al, 2016 ), recruit dendritic cells (DCs) to tumors ( Barry et al, 2018 ; Böttcher et al, 2018 ), and promote neutrophil infiltration into inflamed joints ( Louis et al, 2020 ). On the other hand, NK cells have also been shown to modulate CD4 + T and CD8 + T cell responses in a variety of contexts, ranging from directly pruning activated CD4 + T cells to preventing exaggerated CD8 + T cell responses ( Lang et al, 2012 ; Schuster et al, 2014 ; Waggoner et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%